(untitled) (Journal of Pakistan Orthopaedic Association, 2019)
Objective: To determine the radiological and functional outcome of open reduction and internal stabilization of lateral condyle humerus fracture in children. Methods: This study was conducted in Orthopedic unit, Mardan medical complex, Mardan with a total number of 38 patients. The study duration was from from15 March 2017 to 14 March 2019.All the children had mean age of 6.68 (range; 2-14) years including 25 male and 13 female patients. Among them, 25 patients had Milch Type II while rest had Milch Type I fracture. All the patients were operated and stabilized with k-wire added by the back slab. Plaster removed after 6 weeks and k-wires within 4-6 week. All patients were followed on 2nd, 4th, 6th and at 12th week. At last, follow up the childrens were assessed for the union, carrying angle and elbow range of motion through Hardacre criteria. Results: All fractures united in a mean time of 4.73 weeks with a range of 4-7weeks. Outcomes were excellent in 78.98% patients, good in 18.42 % and poor in 2.63%. No major complication reported in any case. Conclusion: Open reduction and internal stablization with k-wire is an excellent method of fixing lateral condyle fractures in children with excellent radiological and functional results.